2005
DOI: 10.1007/s10072-005-0448-z
|View full text |Cite
|
Sign up to set email alerts
|

Pergolide improvement in neuroleptic-resistant Tourette cases: various mechanisms causing tics

Abstract: The objective was to report the possibility that in Tourette's disorder (TD) the same pathways may not be involved in all patients. Tics in three children affected with TD showed no improvement after treatment with several neuroleptic drugs (D2 blockers) at appropriate doses. However, they did improve greatly and persistently with pergolide treatment. One of the 3 patients showed a less usual tic feature, the most relevant of which resembled violent myoclonias of both upper limbs. This suggests that in these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 7 publications
1
11
0
1
Order By: Relevance
“…Several researchers have reported on many kinds of treatments for tics, including pharmacotherapy and non-pharmacotherapy [16][17][18]. Treatments for comorbid conditions are also important to mitigate tics.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have reported on many kinds of treatments for tics, including pharmacotherapy and non-pharmacotherapy [16][17][18]. Treatments for comorbid conditions are also important to mitigate tics.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggest pergolide as a treatment option for TS (Lipinski et al, 1997). A relevant tic reduction could also be reported in three children (7, 8, and 11 years) using doses of 0.15, 0.20, and 0.25 mg/day, starting with 0.05 mg/day (Cianchetti et al, 2005).…”
Section: Studies On the Effectiveness Of Dopamine Agonists In The Trementioning
confidence: 84%
“…Pergolide, an ergoline DA agonist has been suggested as a treatment option after three patients improved with pergolide (Cianchetti, Fratta, Pisano, & Minafra, 2005). The authors concluded that this improvement might not be associated with an effect on DA-D2-receptors-carrying GABAergic neurons.…”
Section: Dopamine Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…35,36 In the one controlled study of pergolide in TS, 24 youths took a mean dose of 0.2 mg daily for 6 weeks, an amount significantly less than that used in Parkinson's disease. Pergolide increases motor inhibition, decreasing locomotion in rats and restless leg syndrome in human beings.…”
Section: Other Medicationsmentioning
confidence: 99%